2021
DOI: 10.1093/jncics/pkab049
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy Among Adolescent and Young Adult Cancer Survivors

Abstract: The study objective was to identify sociodemographic and coronavirus disease 2019 (COVID-19) factors that are associated with COVID-19 vaccine hesitancy among adolescent and young adult (AYA) cancer survivors. Eligible participants were 18 years or older and were diagnosed with cancer as an AYA (ages 15-39 years) and received services through an AYA cancer program. A total of 342 participants completed a cross-sectional survey. Our primary outcome—COVID-19 vaccine hesitancy—was surveyed as a 5-point Likert sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 10 publications
3
20
2
Order By: Relevance
“…Social factors including a higher exposure to different social-media platforms combined with the behavioral perceptions about the risks of vaccines were the major factors responsible for lower vaccine-acceptance rates in U.S. adults [105]. The educational background was mentioned as the major socio-demographic factor responsible for low vaccine acceptance (63%) among adolescent and young-adult cancer survivors in the U.S. [103]. The behavioral determinants pertaining to the hesitancy towards the COVID-19 vaccine in the U.S. and Canada comprised of misconceptions and misinformation surrounding the efficacy and side effects of the vaccine [106,107].…”
Section: Rates Of Covid-19 Vaccine Acceptancementioning
confidence: 99%
“…Social factors including a higher exposure to different social-media platforms combined with the behavioral perceptions about the risks of vaccines were the major factors responsible for lower vaccine-acceptance rates in U.S. adults [105]. The educational background was mentioned as the major socio-demographic factor responsible for low vaccine acceptance (63%) among adolescent and young-adult cancer survivors in the U.S. [103]. The behavioral determinants pertaining to the hesitancy towards the COVID-19 vaccine in the U.S. and Canada comprised of misconceptions and misinformation surrounding the efficacy and side effects of the vaccine [106,107].…”
Section: Rates Of Covid-19 Vaccine Acceptancementioning
confidence: 99%
“…Although it seems logical that these increased health risks and possible delays in cancer therapy would result in increased uptake of COVID-19 vaccines among survivors, several studies indicate substantial vaccine hesitancy among this population in the United States (U.S.). For example, Waters et al surveyed 342 adolescent and young adult cancer survivors between October 2020 and January 2021, finding that over one-third of respondents (37.1%) reported COVID-19 vaccine hesitancy and that hesitancy was higher among female survivors and survivors with lower educational attainment (Waters, Mann et al, 2021 ). Additionally, in an online national survey of over 6500 blood cancer patients fielded in December 2020 by the Leukemia & Lymphoma Society (LLS), almost 20% of respondents indicated that they would be unlikely or very unlikely to accept a vaccine if it were offered to them for free – with several demographic factors, including younger age, non-White race, female gender, and rural or suburban residence, predicting vaccine hesitancy (Conti et al, 2021 ).…”
Section: Unique Considerations For Covid-19 Vaccination Among Cancer ...mentioning
confidence: 99%
“…Vaccination messages can be delivered by a range of providers including nurses, doctors, and pharmacists and via electronic patient communication portals during both active cancer care and long-term survivorship care, which is important as survivors at different phases of treatment may have varying levels of contact with the health system and obtain care from different types of providers (Institute of Medicine and National Research Council, 2006 ; Mayo et al, 2021 ). Furthermore, different providers might be able to leverage different strengths in recommending vaccines – for example, primary care providers might be able to take advantage of established long-term relationships with survivors and a focus on preventive care (Nekhlyudov, 2021 ), while oncologists may be well-positioned to discuss survivors’ unique vulnerability due to their cancer history, why it is especially important for them to be vaccinated, and any related treatment considerations (Potter et al, 2021 ; Waters, Mann, et al, 2021 ). Consequently, all providers who see individuals with a cancer history should prioritize documenting their vaccine status and encouraging hesitant survivors to consider vaccination.…”
Section: Communication Strategies For Addressing Covid-19 Vaccine Hes...mentioning
confidence: 99%
See 1 more Smart Citation
“…In another report, approximately one third of childhood cancer survivor parents expressed hesitancy in vaccinating their survivors against COVID-19 [ 13 ]. Similarly, in a survey of 342 adolescents and young adult cancer survivors (15–39 years), 37% were vaccine hesitant [ 14 ]. Determining the degree of vaccine hesitancy and distinguishing other reasons for under-vaccination is essential to develop interventions that address substandard vaccine uptake [ 15 ].…”
Section: Introductionmentioning
confidence: 99%